Preventive strategies of SSI: nurses' knowledge in pre-operative and post-operative in surgical site care - Rahmah, Mohd Amin; Myat Moe Thwe, Aung; Sara Yousef, AbuAlkishik (2020)
Some patients’ condition occasionally necessitates medical surgical operations. However, in some cases, the proper care of such resultant surgical sites fails to meet the professional standards due to diverse reasons and knowledge inadequacy. As such, infections are prone to manifest. Nonetheless, many researchers across the globe have sought to determine best nursing practices and ways of preventing such surgical site infections. Hence, this review purposed to detail the current prevention strategies of the surgical site infections and the subsequent improvement approaches within the hospital setups. The previous literature was thus obtained from three major journal databases; CINAHL, PubMed and Medline. Subsequently, the resultant journal articles from the previous researchers consistently confirm the need for strict adherence to the standard operation protocols for the prevention of both pre-operative and post-operative infections. Other measures revolve around hygiene; hand cleaning using antiseptic substances, use of sterile wound dressing materials, use of antiseptic soaps to clean surface. Some studies also confirm the need to remove the wound dressing materials between 24 and 48 hours. Nonetheless, studies also confirm that essence of training to bolster nurses’ knowledge about the prevention strategies of the surgical site infections. Based on such empirical data, it becomes apparent that the prevention measures rotate around the adherence to policies, inculcating strict hygiene and also improving nurses’ knowledge.